NEED GOOD GENES? WE CAN HACK AND RE-ENGINEER THEM - MPRC, Pusat Media & Perhubungan Awam (USM, 2017)
PENANG, 2 May 2017 When we praise people on their good looks or other outstanding traits, saying ‘it must be in your genes’ would be one way of doing so (while we lament ours). Having good genes is the desire of many, but having them would be more to one’s advantage in the future than merely for good looks alone.